Regulation of human T-lymphotropic virus type I latency and reactivation by HBZ and Rex. - Subha Philip; Muhammad Atif Zahoor; Huijun Zhi; Yik-Khuan Ho; Chou-Zen Giam (PLoS Pathogens)
Human T lymphotropic virus type I (HTLV-I) infection is largely latent in infected persons. How HTLV-1 establishes latency and reactivates is unclear. Here we show that most HTLV-1-infected HeLa cells become senescent. By contrast, when NF-κB activity is blocked, senescence is averted, and infected cells continue to divide and chronically produce viral proteins. A small population of infected NF-κB-normal HeLa cells expresses low but detectable levels of Tax and Rex, albeit not Gag or Env. In these "latently" infected cells, HTLV-1 LTR trans-activation by Tax persists, but NF-κB trans-activation is attenuated due to inhibition by HBZ, the HTLV-1 antisense protein. Furthermore, Gag-Pol mRNA localizes primarily in the nuclei of these cells. Importantly, HBZ was found to inhibit Rex-mediated export of intron-containing mRNAs. Over-expression of Rex or shRNA-mediated silencing of HBZ led to viral reactivation. Importantly, strong NF-κB inhibition also reactivates HTLV-1. Hence, during HTLV-1 infection, when Tax/Rex expression is robust and dominant over HBZ, productive infection ensues with expression of structural proteins and NF-κB hyper-activation, which induces senescence. When Tax/Rex expression is muted and HBZ is dominant, latent infection is established with expression of regulatory (Tax/Rex/HBZ) but not structural proteins. HBZ maintains viral latency by down-regulating Tax-induced NF-κB activation and senescence, and by inhibiting Rex-mediated expression of viral structural proteins.